Nigerian Military, Nation-Building and Development, 1979-1999 (British Journal of Multidisciplinary and Advanced Studies, 2025)
The question often asked was: Could the military have been in power without achieving anything? Why did they venture into governance? This was against the background that military rule was variously said to be worse than he worst civilian government. Yet, the military were vindicated after an examination of the roles they played in Nigeria between 1979 and 1999. In the build up to the evolution of the Nigeria’s modern military, it was observed that the military was prodded to take over power from the First Republic political leaders for obvious corruption and nepotism before the eruption of the Biafra-Nigeria civil War (1967-1970). It was concluded that the military acquitted itself through its contributions to peace and unity; and to the task of nation building.